Suicidality among nonadherent patients living with HIV in Buenos Aires, Argentina: prevalence and correlates. Issue 11 (2nd November 2018) - Rodriguez, Violeta J; Sued, Omar; Cecchini, Diego; Mandell, Lissa N; Bofill, Lina M; Weiss, Stephen M; Cassetti, Isabel; Cahn, Pedro; Jones, Deborah L
ABSTRACT: Of those in the general population hospitalized for suicidal ideation and suicide attempts in Argentina, many reattempt suicide and are readmitted. However, few studies in Argentina have examined suicidal ideation and suicide-related behaviors among people living with HIV (PLHIV) and none have examined these factors among nonadherent PLHIV, though the prevalence of suicidal ideation in this group may be higher than in the general population and also than in other groups of PLHIV. This study of PLHIV in Buenos Aires, Argentina, examined the correlates of suicidal ideation in nonadherent PLHIV. Nonadherent patients with HIV ( N  = 118) were recruited from two clinics providing outpatient healthcare services to PLHIV in Buenos Aires, Argentina. Participants completed assessments on demographic characteristics, depression and suicidality, stigma, and self-efficacy. Participants were HIV-infected men (51%) and women (49%) with a median age of 40 years (IQR = 11). About half had completed high school or more, two-thirds were employed, and had a mean monthly income of 4196.79 (SD = 3179.64) Argentine pesos (USD$221). Thirty-three (28% [95% CI 20.3, 37.3]) participants reported suicidal ideation in the past two weeks, and one-third (35.6% [27.1, 44.9]) reported lifetime suicidal ideation. In bivariate analyses, attending a public clinic, being female, younger, unemployed, and experiencing greater stigma and depression were associated with suicidal ideation. In multivariable logistic regression, stigma interacted with the number of years since HIV diagnosis to predict suicidal ideation. The impact of stigma on suicidal ideation decreased with time since HIV diagnosis, suggesting that suicidal ideation may arise following HIV diagnosis due to perception of HIV-related stigma. Interventions to reduce perceived stigma during the period following HIV diagnosis may reduce suicidal ideation in this population. Organizational initiatives that explore HIV stigma microagressions in the healthcare setting may be needed to optimize health outcomes.